Human Biomonitoring of Selected Hazardous Compounds in Portugal: Part II—Lessons Learned on Mycotoxins - Angelina Pena; Sofia Duarte; André M. P. T. Pereira; Liliana J. G. Silva; Célia S. M. Laranjeiro; Marta Oliveira; Celeste Lino; Simone Morais (Molecules, 2021)
Human biomonitoring (HBM) data provide information on total exposure regardless of the route and sources of exposure. HBM studies have been applied to quantify human exposure to contaminants and environmental/occupational pollutants by means of determining the parent compounds, their metabolites, or even their reaction products in biological matrices. HBM studies performed among the Portuguese population are dispersed and limited. Thus, to overcome this knowledge gap, this work reviews the published Portuguese HBM information concerning mycotoxins detected in the urine, serum, milk, hair, and nails of different groups of the Portuguese population. This integrative approach to the available HBM data allows us to analyze the main determinants and patterns of exposure of the Portuguese population to the selected hazardous compounds, as well as to assess the potential health risks. We also aimed to identify the main difficulties and challenges of HBM through the analysis of the enrolled studies. Ultimately, this study aims to support national and European policies in promoting human health by summarizing the most important outcomes and lessons learned through the HBM studies carried out in Portugal.